Evaluación de atrayentes en trampas artesanales para el monitoreo y control de la broca del cafeto (Hypothenemus hampei), en el distrito de Rumizapa, provincia de Lamas - Nolte Macedo, Carlos Augusto (2008)
The objective to evaluate the efficiency of the artisan traps in the monitoreo and control of the coffee borer (Hypothenemus hampei), making use of attractive in the district of Rumizapa, province of Lamas. The present investigation was performing in the ownerships Mr. Genaro Pashanace located in the small village of Chirapa height of kilometer 15 of the highway Fernando Belaunde Terry north; it presents an altitude of 928 msnmm. The present investigation was made completely under a design of blocks randomly. The results demonstrated that contain (metanol + ethanol + coffee worn out parchment) and (metanol + ethanol + coffee pulp) were those better in reducer the population of adult reels, simultaneously it is possible to be reached 6,07 % and 6,06 % of percentage of incidence of the plague. In addition the artisan traps transparencies turned out to be efficient The percentage of reels are captured in the traps and they are females, for to be g the only that fly, therefore its effect in the diminution of the population is high, in addition the artisan trap by its efficiency and reaches of all, is the better appropriate for the Control of the coffe borer.